The YES Holiday Job Rush Campaign : Getting Montreal's Youth into the Workforce - Youth Employment Services (YES) (2009)

Getting Motivated & Staying Focused - Youth Employment Services (YES) (2009)

Projet de formation et de développement des ressources humaines : Rapport annuel - Dialogue McGill (2009)
The McGill Training and Human Resource Development Project contributes to other Quebec government initiatives aimed at ensuring that English-speaking people in Quebec enjoy equitable access, in their own language, to the full range of health and social services available to the general population. Its two main objectives are to ensure effective communication in English between English-speaking Quebecers and the health and social services workers who serve their needs and to increase the number of English-speaking professionals working in the Quebec health and social services system. The Project involves the implementation of four measures in partnership with stakeholders concerned by the issue of access to health and social services in the English-speaking communities. The 2008-2009 year was an extension of the Project which finished in March 2008.

Training and Human Resources Development Project : Annual Report - Dialogue McGill (2009)
The McGill Training and Human Resource Development Project contributes to other Quebec government initiatives aimed at ensuring that English-speaking people in Quebec enjoy equitable access, in their own language, to the full range of health and social services available to the general population. Its two main objectives are to ensure effective communication in English between English-speaking Quebecers and the health and social services workers who serve their needs and to increase the number of English-speaking professionals working in the Quebec health and social services system. The Project involves the implementation of four measures in partnership with stakeholders concerned by the issue of access to health and social services in the English-speaking communities. The 2008-2009 year was an extension of the Project which finished in March 2008.

YES E-Newsletter : June 2009 - Youth Employment Services (YES) (2009)
Number of pages: 2

YES E-Newsletter : May 2009 : Volume 1 : Issue 5 - Youth Employment Services (YES) (2009)
Number of pages: 4

YES E-News : April 2009 - Youth Employment Services (YES) (2009)
Number of pages: 1

Transformation Through Lifelong Learning: A Path to Change - Quebec Association for Adult Learning (QAAL) (2009)

Dialogue : Better Communication for Better Care - Dialogue McGill (2009)
Number of pages: 4

Dialogue : Mieux communiquer pour mieux soigner - Dialogue McGill (2009)
Number of pages: 3

Winter/Spring 2009 Program Book - Youth Employment Services (YES) (2009)

Congrès des Fournisseurs de Sercices d'emploi du Québec (2008)

Quebec Employment Service Providers Conference (2008)

Training and Human Resources Development Project : Annual Report - Dialogue McGill (2008)
The McGill Training and Human Resource Development Project contributes to other Quebec government initiatives aimed at ensuring that English-speaking people in Quebec enjoy equitable access, in their own language, to the full range of health and social services available to the general population. Its two main objectives are to ensure effective communication in English between English-speaking Quebecers and the health and social services workers who serve their needs and to increase the number of English-speaking professionals working in the Quebec health and social services system. The Project involves the implementation of four measures in partnership with stakeholders concerned by the issue of access to health and social services in the English-speaking communities. The 2008-2009 year was an extension of the Project which finished in March 2008.

Lost in Translation - Buffitt, Kimberly; Lanyi, Danille (2008)

The Training and Retention of Health Professionals Project - Dialogue McGill (2008)

The 11th YES Entrepreneurship Conference : March 8/2008 - Youth Employment Services (YES) (2008)

Stepping into the Future : L’avenir entre nos mains - Carrefour jeunesse-emploi NDG; Table de concertation jeunesse NDG (NDG Community Council (NDGCC), 2008)
Community‐based planning to facilitate the socio‐professional integration of youth between the ages of 16 ' and 30 in Notre‐Dame‐de‐Grâce, Côte‐Saint‐Luc, Hampstead and Montreal‐West. A project of the Carrefour jeunesse‐emploi NDG and the Table de concertation jeunesse NDG, in collaboration with Service Canada

Dialogue : Better Communication for Better Care - Dialogue McGill (2008)
issued: Spring, 2008/Summer, 2008 Number of pages: 7

Dialogue : Mieux communiquer pour mieux soigner - Dialogue McGill (2008)
issued: Spring, 2008/Summer, 2008 Number of pages: 5

A Policy Framework for Economic Development and Employability for the English-speaking Communities of Quebec : Submitted to the Quebec Community Groups Network (QCGN) - Qu'anglo (2008)
Through previous research and following a number of community consultations, the QCGN had determined that there is a need for initiatives that will enable the English-speaking Communities of Quebec to work more effectively with the Government of Canada, the Government of Quebec, school boards and relevant stakeholders to more fully participate in the economy of province. Given the continuing exodus of educated and trained anglophones to seek employment opportunities elsewhere, and the difficulties faced by particular segments of the population, especially youth, visible minorities and newly arrived immigrants, who choose to seek employment and self-employment within Quebec, it was determined that an integrated and targeted approach to improve the economic development prospects of the community was required.
Keywords: Official Language Minority Community (OLMC)

Fall 2008 Program Book - Youth Employment Services (YES) (2008)

Winter/Spring 2008 Program Book - Youth Employment Services (YES) (2008)

Training and Human Resources Development Project : Annual Report - Dialogue McGill (2007)
The McGill Training and Human Resource Development Project contributes to other Quebec government initiatives aimed at ensuring that English-speaking people in Quebec enjoy equitable access, in their own language, to the full range of health and social services available to the general population. Its two main objectives are to ensure effective communication in English between English-speaking Quebecers and the health and social services workers who serve their needs and to increase the number of English-speaking professionals working in the Quebec health and social services system. The Project involves the implementation of four measures in partnership with stakeholders concerned by the issue of access to health and social services in the English-speaking communities. The 2008-2009 year was an extension of the Project which finished in March 2008.

YES E-News : September 2007 - Youth Employment Services (YES) (2007)
Number of pages: 1

Discussion Document #1 : Demographics and the Long-term Development of the English-speaking Communities of the Greater Montreal Region - Quebec Community Groups Network (QCGN); Greater Montreal Community Development Initiative (GMCDI) (2007)

Creating Sustainable Initiatives to Retain and Maintain Health and Social Services Professionals on the Lower North Shore - Lavallée, Marissa (Coasters Association, 2007)
The Coasters Association, in partnership with the Centre de Sant et de Services Sociaux de la Basse-C te-Nord (CSSSBCN), received a Training and Human Resources Development Project from McGill University, for seven weeks from February 13th to March 31st, 2006, Phase 1, under the Retention and Distance Professional and Community Support Program, to conduct a needs assessment on the issue of hiring and retaining English Professionals on the Lower North Shore. The objective of this needs assessment was to develop Phase II which is a two-year proposal that would lead to the improvement of hiring and retaining Health and Social Services Professionals on the Lower North Shore. The long term intended outcome is the increase in access to Health and Social Services for English speaking residents on the territory. Another objective of this needs assessment is to contact institutional and community-based objectives (i.e Education & Health and Social Services) it is hoped that these contacts will lead to partnerships that will help to address the hiring and retention of English-speaking Professionals on the Lower North Shore.
Parallel title: Measure 2 : Retention and Distance Professional and Community Support Program November 6 2006 to March 31 2007

The 10th Anniversary YES Entrepreneurship Conference : March 3/2007 - Youth Employment Services (YES) (2007)

Dialogue : Better Communication for Better Care - Dialogue McGill (2007)
issued: Spring, 2007/Summer, 2007 Number of pages: 7

Dialogue : Mieux communiquer pour mieux soigner - Dialogue McGill (2007)
issued: Spring, 2007/Summer, 2007 Number of pages: 5

Report of the Greater Montreal Community Development Initiative Steering Committee : Building Upon Change and Diversity within the English-speaking Communities of the Greater Montreal Region: - Greater Montreal Community Development Initiative (GMCDI) (Quebec Community Groups Network (QCGN), 2007)
In the 30 years since the passage of Bill 101, the nature of the English-speaking communities of the Greater Montreal Area has changed dramatically. The evolution of the largest linguistic minority within a linguistic minority in Canada has resulted in the emergence of certain unique challenges and opportunities. It was to address these issues that the Greater Montreal Community Development Initiative (GMCDI) was launched. This initiative, funded by the Department of Canadian Heritage, is intended to assist the English-speaking communities of the Greater Montreal Area in identifying shared community development challenges and priorities, and the most effective strategies to address them.
Keywords: Official Language Minority Community (OLMC)

Special Needs Project - Lavallée, Marissa (2007)

Program Book: Winter / Spring 2007 - Youth Employment Services (YES) (2007)

Self-Employment and Employment in Quebec's English-speaking Cultural Communities and Visible Minorities : Prospects and Problems - Jedwab, Jack (Youth Employment Services (YES), 2006)
What are the principal barriers to self-employment and employment for members of Quebec’s English-speaking visible minorities and cultural communities? The question is considered in this report in view of the ongoing challenges that some members of English-speaking visible minorities and cultural communities face in the current economy. The specific aim is to improve our understanding of factors which prevent members of Quebec’s English-speaking visible minorities and cultural communities from achieving self-employment and employment goals.

Language Training Program : Findings and recommendations of the lexicon evaluation committee - McLaughlin, Sky; Rogers, Jim (Lexicon Evaluation Committee, 2006)

Skills and Thrills - Gallibois, Kris (Coasters Association, 2006)
The main goal of this project was to develop leadership skills in the youth in St. Augustine ages 12-17. I held meetings with the youth, conducted workshops on leadership and decision making skills, decided upon a goal to accomplish and a plan to carry out the said goal. Also, I held fun sessions wherein the youth participated in activities and games.

A Needs Assessment on the Issue of Hiring and Retaining English Professionals on the Lower North Shore - Coasters Association (2006)
The Coasters Association, in partnership with the Centre de Santé et de Services Sociaux de la Basse- Côte-Nord (CSSSBCN), received a Training and Human Resources Development Project from McGill University for seven (7) weeks from February 13 to March 31, 2006, under the Retention and Distance Professional and Community Support Program, to conduct a needs assessment on the issue of hiring and retaining Professionals, not only English-speaking - but Bilingual Professionals as well, on the Lower North Shore of Quebec. The objective of this needs assessment was to develop Phase II which is a two year proposal that would lead to the improvement of hiring and retaining professionals on the territory. The long term intended outcome is the increase in access to Health and Social Services for English speaking residents on the Lower North Shore. Another objective of this needs assessment is to make contact with institutional and community based organizations (ie: Education and H.&S.S.), it is hoped that these contacts will lead to long term partnerships and commitment to addressing the hiring and retention of English and/or Bilingual Professionals on the Lower North Shore.

BCRC Newsletter - Black Community Resource Centre (BCRC) (2006)
Number of pages: 7

6th Montreal Self-Employed Artists Conference - Youth Employment Services (YES) (2006)

BCRC Newsletter - Black Community Resource Centre (BCRC) (2005)
Number of pages: 6

BCRC Newsletter - Black Community Resource Centre (BCRC) (2005)
Number of pages: 7

Training and Human Resources Development Project : Measure 1 : Language training program - Dialogue McGill (2005)
The language training program presented is part of the Training and Human Resources Development Project that McGill University is to implement. This project is designed to ensure that English-speaking Quebecers obtain equitable access, in their language, to the range of health and social services offered to the entire population. The project has been elaborated against a backdrop of sociodemographic changes affecting Québec’s English-speaking communities, the adoption of new legislation modifying the organization of work, and the modernization of the health and social services system. It will be geared to clinical projects now being prepared pertaining to the organization of services. The project is an additional means of reviewing and implementing regional programs of access to health and social services in the English language, as stipulated by the Act respecting health services and social services.

The Development of an Action Plan to Expand Volunteerism & Leadership on the Lower North Shore of Quebec - Buckle, Heidi (Coasters Association, 2005)
Throughout phase one of this project, a needs assessment study was successfully carried out to identify the needs of the one hundred and thirteen (113) community organizations and twenty-one (21) regional organizations on the coast; along with a volunteer awareness campaign and the building of a strong volunteer base for the fifteen (15) communities of the Lower North Shore of Quebec. This study was then distributed to all the organizations, the working group, the Board of Directors of the Coasters Association and the volunteers who participated in this project. It has been shared with various Quebec Community Group Networks and HRD Community Table groups across the province, along with various federal and provincial government departments. It has been used as a working tool by many organizations on and off the coast.

The English-speaking Catholic Population Profile in Quebec, 2001 : Comparative Analysis of the Demographic Characteristics and Geographic Distribution of the FOLS-English Catholic Population in Quebec - Ahmadzadeh, Nazanin (English Speaking Catholic Council, 2004)
The general objective of this study is to provide the English-Speaking Catholic Council in Québec with a comprehensive demographic portrait of the English speaking Catholic Community in Québec. This portrait will serve as support for the orientation of the ESCC. This study follows a previous study carried out in 1992 which focused only on the parishes in the Montreal metropolitan area.

The English-Speaking Catholic Population in Quebec, 2001 - Ahmadzadeh, Nazanin; Warnke, Jan (2004)

A Report on the Quebec Fishing Community Adjustment Measures (QFCAM) Project - Blanche, Diana (Coasters Association, 2003)
The following report is a compilation of information pertaining to the activities under taken by the participants of the Fishery Restructuring Program.

Global Development Plan : Strategy to Revitalize the English-language Minority Communities of Quebec : Sector Plans - Quebec Community Groups Network (QCGN) (2003)
The roots of the English-speaking community in Quebec go back nearly 250 years, and have a historic place in the development of the province. While English-speaking communities traditionally established their own institutions in the areas of religion, education and health and social services, that type of community engagement dissolved to a greater extent with the Quiet Revolution and the emergence of the modern Quebec state. Now, after 30 years of exodus and isolation, the time has come for the English-speaking community to become involved, to re-establish its presence in the policy and program decision-making areas that affect the daily lives of its members.

Global Development Planning : Strategy to Revitalise the English Language Minority Communities of Quebec : Education & Training - Quebec Community Groups Network (QCGN) (2003)
The following Plan has been prepared by the Education & Training Task Force - one of eight sector task forces which bring together leading representatives from across the Province committed to the preparation of a Global Development Plan for the Englishspeaking minority communities of Quebec.

Leadership Handbook - Quebec Federation of Home and School Associations (QFHSA) (2003)

Brief to the Estates General on the French Language - Alliance Quebec (AQ) (2001)
In 1982, following its long tradition of creating organizations and institutions to meet its needs and fulfill its aspirations, the English-speaking community created Alliance Quebec to respond to the dramatic changes in Quebec's society. Alliance Quebec is a non-profit, volunteer-based, community organization committed to the preservation and enhancement of the English-speaking communities and it's institutions in Quebec. Alliance Quebec serves as voice on public policy for the English-speaking communities. To that end, we strive for acceptance of an open and multicultural society; a commitment to a united Canada; a participative and integrated approach toward community retention and development; and proactive and entrepreneurial management.

Alliance Quebec Presents Equity Brief to Quebec National Assembly - Alliance Quebec (AQ) (2000)

Brief on Draft Law Number 143 Equity in the Civil Service - Alliance Quebec (AQ) (2000)
As the Committee studying draft law 143 is aware, Alliance Quebec is an association which lobbies governments at all levels for the rights and needs of the Englishspeaking population of Quebec to be respected. Our organization has chapters in Montreal, West Island, East Island, South Shore, Laval, Rouyn-Noranda, Val d'Or, Saguenay Lac Saint Jean, Mauricie and the Upper and Lower Laurentians. We also have our provincial youth commission that represents young people province-wide. In all, over 83 percent of Quebec's English-speaking population resides in Alliance Quebec territory.

Alliance Quebec Supports Superior Court Ruling on Computer Software Case - Alliance Quebec (AQ) (2000)

Conference on Job Equity and Employability - Johnson, William (2000)

A Brief on Quebec's English-speaking Youth on the Occasion of the Youth Summit - Alliance Quebec (AQ) (2000)
We, the English-speaking youth of Quebec, come before you today to ask that our distinctive voices be heard. We share many of the concerns, problems and preoccupations of our French-speaking brothers and sisters. But we have anguishes, specific and poignant, which are ours alone, and which you will not hear about from the other participants and observers at the Youth Conference.